2008
DOI: 10.1590/s1517-70762008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the effect of some straight biological oils on cutting force during cylindrical turning

Abstract: Cutting fluids of various types are usually employed to control the heat generated in machining. The continued application of conventional petroleum based metal working fluids is being challenged by the need to reduce overall volume of fluids, minimize health risks and bio-contamination. Bio-oils assisted machining is an environmental bio-compatible technology for desirable control of temperature. This paper investigates the effect of some vegetable based oils on cutting force during cylindrical machining of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…3 Biological oil cutting fluid has several superior features compared to the petroleum-based cutting fluids, such as, reduced overall volume of fluids due to higher viscosity, minimized health risk to workers and minimized biocontamination. 4 Vegetable oils are particularly effective as boundary lubricants as the high polarity of the entire base oil allows strong interactions with the lubricated surfaces. However, the main weakness is their relatively poor oxidation stability.…”
Section: Introductionmentioning
confidence: 99%
“…3 Biological oil cutting fluid has several superior features compared to the petroleum-based cutting fluids, such as, reduced overall volume of fluids due to higher viscosity, minimized health risk to workers and minimized biocontamination. 4 Vegetable oils are particularly effective as boundary lubricants as the high polarity of the entire base oil allows strong interactions with the lubricated surfaces. However, the main weakness is their relatively poor oxidation stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, Soy-based metalworking �uid had slightly higher tapping torque efficiency in the semisynthetic form compared to others. As cutting �uids, ground nut and Shea butter oils generated lower cutting forces and coefficient friction while turning mild steel, aluminum, and copper workpieces [11]. �etter surface �nish is also reported under these oils.…”
Section: Introductionmentioning
confidence: 86%
“…Sen et al [48] showed the benefits of applying MQL with vegetable oil, and the advanced modeling technique to establish a beneficial manufacturing system. Ojolo et al [49] performed an experimental work to find out the influences of vegetable oil viz. groundnut oil, palm oil, kernel oil, shear butter oil and coconut oil on cutting forces during machining of mild steel, copper, and aluminium.…”
Section: Performance Of Vegetable Oils In Mql Assisted Machiningmentioning
confidence: 99%